Estrategias para la prevención de bullying cibernético en la Unidad Educativa Sagrado Corazón de Jesús. - Pazmiño Torres, Cristina Jessenia (2023)
The internet is a space in which each one of us has created an imaginary life, but the misuse of social networks can lead to poor digital communication; in this context, cyberbullying stands out since 2004. Within educational institutions, it has been observed that students also present this aggressive behavior on the Internet, by making some kind of "jokes" that become offensive or even harassing against some of their classmates, turning this into cyberbullying, a problem that before it was only called bullying because no digital media was used for this; From this situation was born the initiative to carry out this study to students of the third year of high school of the Sacred Heart of Jesus Educational Unit of the city of Latacunga, province of Cotopaxi, to create some digital communication strategies that were practiced to prevent cyberbullying in this group of students.